Modification of Cassava Peel Starch, Substituting Chitosan and Seaweed: Production of High Quality Edible Film - Hamsina; Friska Doan; Hermawati; Ifa Safira; Ruslan Hasani (Postgraduate, University of Mataram, 2024)
Biodegradable packaging materials from biomass have been proven to be effective and efficient in improving the quality of materials food because it has the advantages of long shelf life, biodegradable, safe for health and cheap easy to use. The aim of the research is to determine the best formulation and water vapor rate properties as well as the mechanical properties of edible film based on cassava peel starch with the addition of palm oil and chitosan. The method used to determine the best formulation of edible film by making cassava peel starch, mixing raw materials and printing edibles film. Next, the water vapor rate and mechanical properties tests were carried out which included tensile strength tests, elongation tests and biodegradation tests. Results What was obtained from this research was the optimum concentration, namely 5 gr of cassava starch, 2 ml glycerol, 2 grams chitosan and 1 ml Palm oil with edible film characteristics was obtained respectively for the water vapor transmission rate test of 15.37 gr/hour.m2, tensile strength test of 0.66 MPa, elongation test of 4.05%, thickness test of 0.17 mm, and biodegrability test for 2 Sunday.